Identification of Key Genes and Pathways in RBCK1 Deficient patients by Gene Expression Profiling - Khyber Shinwari; Mikhail A. Bolkov; Irina A. Tuzankina; Valery A. Chereshnev (Acta Medica Iranica, 2021)
HOIL-1/RBCK1 deficiency is a new autosomal receive disorder with unstable cellular responses to pro-inflammatory cytokines, resulting in auto-inflammation, pyogenic bacterial disease, as well as the development of muscular amylopectinosis. This study explored the molecular mechanisms of RBCK1 deficiency with integrated bioinformatics analyses of the feature genes and the correlative gene functions. The expression profile of GSE24519 was downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) between RBCK1, MYDK88, NEMO deficient fibroblast, and healthy fibroblast specimens were identified. Gene ontology (GO) enrichment analysis on gene functions and the Kyoto Encyclopedia of Gene and Genome (KEGG) pathway analysis were performed by using Database for Annotation, Visualization, and Integrated Discovery (DAVID). Cytoscape was used to visualize the protein-protein interaction (PPI) of these DEGs. GO analysis revealed that the “Skeletal system development, Extracellular matrix organization, Positive regulation of cell migration, Negative regulation of canonical Wnt signaling pathway, Cell adhesion, Angiogenesis and Negative regulation of BMP signaling pathway, Serine-type carboxypeptidase activity, Polysaccharide binding, Calcium ion binding, frizzled binding, Neuropilin binding, and cell adhesion molecule binding, extracellular exosome, extracellular space, extracellular region, lysosomal lumen, endoplasmic reticulum lumen, cell surface and focal adhesion to BP, MF, and CC, respectively. The KEGG pathway analysis showed that the complement and coagulation cascade, ECM receptor interactions, PI3K- Akt signaling pathway, PPAR signaling pathway, TGF-beta signaling pathway, Pathway in Cancer, Viral carcinogenesis and Focal adhesion pathway were closely associated with RBCK1 deficiency occurrence. Importantly, TK1, AURKB, CDCA2, UBE2C, KIFC1, CEP55, CDCA3, GINS2, MCM6, and CDC45 were predicted to be significantly related to RCBK1 deficiency. Our discovery provides a registry of genes and pathways that are disrupted in RCBK1, which will enhance in understanding the pathogenesis of RBCK1 deficiency and other innate immunodeficiency diseases. This study has the potential to be used in the clinic for diagnosis and targeted therapy of RCBKI and other innate immunodeficiencies in the future.